Elevated Serum IgG4 Levels in a Young Patient with Polyserositis and Necator americanus Infection - Giuseppe D. Sanna; Roberto Manetti; Valentina de Filippo; Sergio Babudieri (Case Reports in Immunology)
IgG4-related disease is a fibroinflammatory systemic condition characterized by tumefactive lesions, lymphoplasmacytic infiltrate rich in IgG4-positive plasma cells, storiform fibrosis, and elevated serum IgG4 concentrations. It has been described in virtually every organ system. Autoimmunity and infectious agents are potential immunologic triggers in IgG4-related disease. Herein, we describe a peculiar case of effusive-constrictive pericarditis in an 18-year-old boy with polyserositis and concomitant Necator americanus infection.